Penerapan senam otak terhadap daya ingat (fungsi kognitif) pada lansia yang mengalami demensia di wilayah kerja puskesmas - Pangesti, Dimas Ning; Wulan, Sarinah Sri; Marliyana, Marliyana (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Ikatan Dokter Indonesia (IDI), 2025)
Background: Dementia is a generalized decline in higher mental functions that is progressive and irreversible with a lot of consciousness. Cognitive is a person's belief about something that is obtained from the process of thinking about someone or something. Brain exercise can improve language skills and memory. Purpose: To determine the results of the application of brain exercise on cognitive function in the elderly with dementia with 2 elderly subjects. Method: This type of qualitative writing uses a case study approach. Results: The application of brain exercise on subjects I and II after brain exercise were carried out, namely, on subject I, an increase in day 5 was found with a total MMSE assessment score of 28 (normal cognitive function). Meanwhile, respondent II got the results on the 5th day with a total score of 24 (mild dementia). Conclusion: The difference in results between the two subjects was due to the factors that influenced it, namely, education and physical activity. Keywords: Brain Exercise; Cognitive; Dementia; Elderly. Pendahluan: Demensia adalah penurunan menyeluruh darifungsi mental luhur yang bersifat progresif dan ireverisibel dengan kesadaran yang banyak. Kognitif adalah kepercayaan seseorang tentang sesuatu yang didapatkan dari proses berpikir tentang sesorang atau sesuatu. Senam otak mampu meningkatkan kemampuan berbahasa dan daya ingat. Tujuan: Untuk mengetahui hasil penerapan senam otak terhadap fungsi kognitif pada lansia yang mengalami demensia dengan 2 orang subjek lansia. Metode: Jenis penulisan kualitatif menggunakan pendekaatan studi kasus. Hasil: Penerapan senam otak pada subjek I dan II sesudah dilakukan senam otak yaitu, pada subjek I ditemukan peningkatan hari ke-5 dengan jumlah skor penilaian MMSE 28 (fungsi kognitif normal). Sedangkan responden II didapatkan hasil hari ke-5 dengan jumlah skor penilaian 24 (demensia ringan). Simpulan: Terjadinya perbedaan hasil antara kedua subjek karena adanya faktor-faktor yang mempengaruhinya yaitu, pendidikan dan aktivitas fisik. Kata Kunci: Demensia; Kognitif; Lansia; Senam Otak.